2020
DOI: 10.3390/f11111218
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes of Softwood Floodplain Forests—Did the Disappearance of Wet Vegetation Accelerate the Invasion Process?

Abstract: Objectives: We followed the long-term changes of softwood floodplain forests strongly altered by water regime changes and examine the behaviour of neophytes in this environment. Here we ask: (1) How did the composition of neophyte and native species change? (2) How did the presence of species that prefer wetter conditions change? (3) What traditionally distinguished type of softwood floodplain forests (a wetter one or a more mesophilous one) do neophytes prefer? (4) What environmental factors affect the native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…They discovered these changes were mainly caused by the disturbance of the water regime. They concluded that, during the period monitored, there was a decline in autochthonous species and an increase in neophytes, which are slowly dominating domestic species (Mikulová et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered these changes were mainly caused by the disturbance of the water regime. They concluded that, during the period monitored, there was a decline in autochthonous species and an increase in neophytes, which are slowly dominating domestic species (Mikulová et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the National Forest Inventory and Monitoring (NIML) of the Slovak Republic, which also included the so-called "white areas" (forests on non-forested land), Slovakia's forest cover is up to 44.3 ± 0.4%, which is positive, but they do not reflect the structural changes that have occurred during that period (Ministry of Agriculture and Rural Development of the Slovak Republic, 2010). Mikulová et al (2020) has stated that in the last 60 years, soft floodplain forests have been transformed considerably. The plant composition points to the indirect intervention of…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, riparian vegetation, e.g., floodplain vegetation or vegetation directly adjacent to rivers and streams, influences several ecological functions of aquatic habitats, such as providing food, moderating stream water temperature by evapotranspiration and shading, providing a buffer zone that filters sediments and controls nutrients, and stabilizes stream banks [72,74,80,81]. Moreover, riparian zones represent key systems for regulating aquaticterrestrial linkages [72,74,82,83] which may provide early indications of environmental change [74,84,85].…”
Section: Riparian Habitatsmentioning
confidence: 99%
“…Changing climate results in a higher frequency and intensity of disturbance events such as storms (Beniston et al, 2007), droughts (Dubrovský et al, 2014;Hanel et al, 2018;Seidl et al, 2017), and floods (Arnell and Gosling, 2016;Dottori et al, 2018;Winsemius et al, 2016), influences habitat suitability for local forest communities (Dyderski et al, 2018), and alters interactions between pests and diseases (Bentz et al, 2010;Jönsson et al, 2009). Furthermore, globalization favors the accidental spread of non-native species (Hulme, 2009;Meyerson and Mooney, 2007;Mikulová et al, 2020) which include pests and diseases that endanger forest tree species and biodiversity (Boyd et al, 2013) as well as non-native plants (Allard and Sigaud, 2005;Nisbet et al, 2015) that create competitive pressure on native plant communities (Nadal-Sala et al, 2019). Both impacts were found to go beyond the capability of native species and ecosystems to resist (Hansen, 2008).…”
Section: Introductionmentioning
confidence: 99%